The Effect Of The Perceptıon Of Employees About Theır Managers’ Humor Styles On Job Satısfactıon - Rüzgar, Nilüfer (Archives of Business Research, 2018)
Effective management of human, which is the most important resource of organizations, leads to increasing overall performance of the organizations and thus, gaining competitive advantage. In this sense, watching employees’ desires and needs, in order not to unstabilize their job-life balance, which increases their job satisfaction, is one of the most crucial topics that needs to be paid attention by organizations so as to be powerful and eternal. Furthermore, adopting and using positive and negative humor styles in organizations, along with the perception of employees about their managers’ humor styles, has recently drew attention and been researched in literature. Positive humor styles are thought to increase employees’ job satisfaction, while negative humor styles are believed as having a decreasing effect on employees’ job satisfaction. In this research, the perceptions of employees about their managers’ humor styles and its effect on their job satisfaction is researched. In the frame of the research, local and foreign organizations, performing in production and service sector in the city of Bursa, Turkey, are evaluated as population. In this sense, a comparison is made between two sectors in terms of analyses results. In terms of measurement, Martin and Puhlik-Doris (2003)’s Humor Styles Questionnaire (HSQ) and Weiss et.al. (1967)’s Minnesota Job Satisfaction Questionnaire are used.